2009
DOI: 10.3758/app.71.6.1228
|View full text |Cite
|
Sign up to set email alerts
|

Categorization reduces the effect of context on hedonic preference

Abstract: When moderately hedonically positive test stimuli are presented following better-liked context stimuli, preferences between the test stimuli are reduced. This reduction in preference, hedonic condensation, occurs in settings that also produce negative hedonic contrast--the phenomenon in which moderately hedonically positive test stimuli seem less positive when they follow better-liked context stimuli. Subjects who were instructed that the context and test stimuli were from different categories exhibited less h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…These results show that hedonic condensation and hedonic expansion occur when using the same two sets of images of faces, which occupy opposite sides of the hedonic scale. These results expand the findings of previous studies which showed hedonic condensation and hedonic expansion with juices, images of birds, and paintings (Zellner et al, 2006(Zellner et al, , 2009(Zellner et al, , 2010. The results also support the idea that hedonic condensation and hedonic expansion accompany positive and negative hedonic contrast, since participants in this study saw the same stimuli as did participants in experiment 1 of Cogan et al (2013), where hedonic contrast in both directions was found.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results show that hedonic condensation and hedonic expansion occur when using the same two sets of images of faces, which occupy opposite sides of the hedonic scale. These results expand the findings of previous studies which showed hedonic condensation and hedonic expansion with juices, images of birds, and paintings (Zellner et al, 2006(Zellner et al, , 2009(Zellner et al, , 2010. The results also support the idea that hedonic condensation and hedonic expansion accompany positive and negative hedonic contrast, since participants in this study saw the same stimuli as did participants in experiment 1 of Cogan et al (2013), where hedonic contrast in both directions was found.…”
Section: Discussionsupporting
confidence: 91%
“…Experiment 2 expanded on the findings of Zellner et al (2009), which showed that hedonic condensation of hedonically positive stimuli could be influenced by categorization. These results show that, when subjects were instructed to categorize stimuli into two separate categories, the effect of context stimuli on attractiveness difference judgments of the target stimuli was eliminated for the attractive targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When positive context stimuli are presented before a set of more hedonically neutral test stimuli, both negative hedoni c contrast (Parker, Bascom, Rabinovitz, & Zellner, 2008;Rota & Zellner, 2007;Zellner, Rohm, Bassetti, & Parker, 2003) and a decrease in preference between test stimuli (i.e., hedonic condensation) occur (Zellner, Allen, Henley, & Parker, 2006;Zellner, Mattingly, & Parker, 2009). So negative hedonic contrast and hedonic condensation cooccur when good stimuli precede less good stimuli.…”
mentioning
confidence: 99%